Learning probabilistic graphical models in R : familiarize yourself with probabilistic graphical models through real-world problems and illustrative code examples in R /: familiarize yourself with probabilistic graphical models through real-world problems and illustrative code examples in R. (2016) - Bellot, David
No abstract available